Development of a quality by design-based ultra-performance liquid chromatography method for the simultaneous estimation of casirivimab and imdevimab with greenness metrics - Sravanthi Gandu; Kumaraswamy Gandla (Green Analytical Chemistry)
This study presents the development and optimization of an ultra-performance liquid chromatography method for the simultaneous analysis of casirivimab and imdevimab, guided by the principles of Quality by Design. Initial method development trials explored various mobile phase compositions, with ethanol chosen as the organic solvent due to its cost-effectiveness. A series of optimization steps, including the substitution of orthophosphoric acid with formic acid, were employed to improve peak resolution and chromatographic performance. A comprehensive risk assessment was conducted to identify critical method parameters, which were then subjected to screening and optimization using a design of experiments approach. The taguchi orthogonal array design was used to assess the influence of factors such as flow rate, column temperature, and organic phase percentage on critical analytical attributes, including retention time, tailing factor, theoretical plates, and resolution. The optimization process identified optimal conditions of 60 % ethanol, a flow rate of 0.2 mL/min, and a column temperature of 30 °C. Method validation demonstrated excellent linearity (R² > 0.999), low detection limits (Limit of detection and Limit of quantification), and good reproducibility, with percentage relative standard deviation values below 2 %. Forced degradation studies confirmed the method's stability-indicating capability, and the method was successfully applied to determine casirivimab and imdevimab in a commercial formulation. Additionally, the greenness of the method was assessed using the various tool, highlighting its minimal environmental impact. The proposed ultra-performance liquid chromatography method offers high precision, accuracy, and reliability, making it suitable for quality control and routine analysis of casirivimab and imdevimab in monoclonal antibodies cocktails.